2017
DOI: 10.1080/19338244.2017.1395789
|View full text |Cite
|
Sign up to set email alerts
|

Impact of work pressure, work stress and work–family conflict on firefighter burnout

Abstract: Little research has explored burnout and its causes in the American fire service. Data were collected from career firefighters in the southeastern United States (n = 208) to explore these relationships. A hierarchical regression model was tested to examine predictors of burnout including sociodemographic characteristics (model 1), work pressure (model 2), work stress and work-family conflict (model 3) and interaction terms (model 4). The main findings suggest that perceived work stress and work-family conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 40 publications
5
66
0
7
Order By: Relevance
“…A supportive organizational climate can serve as a potential force to alleviate conflict when it arises. The present study found that WFC was positively correlated with teacher burnout, which was consistent with previous studies (48)(49)(50). Bagherzadeh et al (24) reported that there was a significantly negative association between WIF and overall burnout, FIW was significantly associated with depersonalization.…”
Section: Discussionsupporting
confidence: 92%
“…A supportive organizational climate can serve as a potential force to alleviate conflict when it arises. The present study found that WFC was positively correlated with teacher burnout, which was consistent with previous studies (48)(49)(50). Bagherzadeh et al (24) reported that there was a significantly negative association between WIF and overall burnout, FIW was significantly associated with depersonalization.…”
Section: Discussionsupporting
confidence: 92%
“…Control variables. Based on previous research, we included gender (0 = male, 1 = female), education (1 = college or below, 2 = bachelor degree, 3 = master’s degree or above), and age (years), because of their potential influences on emotional exhaustion [35,36].…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, their levels of exhaustion and overall burnout were increased after putting out the fire. Exposure to intense trauma situations, such as a fire, a traffic accident or a natural disaster, seems to take a toll on firemen's feelings of exhaustion and fatigue, and make them feel inadequate or unable to envision and implement suitable solutions (Lourel et al, 2008;Mitani et al, 2006;Smith et al, 2017). The potential preventive role of enhancing fire service workers' flow along with their hope levels as a measure against anticipated burn out increases sets a fruitful avenue for further empirical research.…”
Section: Discussionmentioning
confidence: 99%
“…Since firefighters are among the first responders in case of fire, extrication after massive natural disasters or traffic accidents, it has been well established that they may exhibit signs of fatigue, exhaustion, even changes in sleep patterns (Lourel, Abdellaoui, Chevaleyre, Paltrier, & Gana, 2008;Mitani, Fujita, Nakata, & Shirakawa, 2006;Smith, Hughes, DeJoy, & Dyal, 2018). Burnout in firemen may also manifest in psychological and social ways, such as alienation, compassion fatigue, doubting one's professional identity, work stress, fighting with family members and being prone to accidents during work (Huynh, Xanthopoulou, & Winefield, 2013;Katsavouni, Bebetsos, Malliou, & Beneka, 2015;Smith, DeJoy, Dyal, & Huang, 2017).…”
Section: Introductionmentioning
confidence: 99%